Awareness and Practices of Oral Hygiene among Female Undergraduates in a Malaysian University - Zarina Waheed; Munazza Saeed; Rafey Ahmad Jameel (Journal of Education and Educational Development, 2020)
The aim of this study is to evaluate the extent of awareness and practices of oral hygiene among undergraduate female students in a residential college of a university at Malaysia and to assess the need for awareness programs about oral hygiene. The study was carried out using a self-administered questionnaire. Hundred undergraduate female Malay students were selected as sample through convenience sampling. The results indicated that a majority of the respondents used toothpaste and toothbrush as primary tools for cleaning their teeth twice a day and was found that they had never used Miswak (a wooden teeth-cleaning stick made from tree twigs). They had adequate knowledge about periodontal and gingival health and were aware of the importance of visiting dentist regularly; however, most of them visited dentists when having a toothache. They had also reported need for organizing oral hygiene awareness programs by college administration and showed adequate oral hygiene knowledge and practices. Nevertheless, few inadequate practices were also identified which were being considered under oral hygiene along with lack of awareness programs being organized in college for which recommendations are suggested.
Keywords: wareness; females; oral hygiene; practices